The presence of beneficial insects and damage intensity of cocoa pod borer (Conopomorpha cramerella Snellen) in plantations with and without insectary plants - Sjam, Sylvia; Dewi, Vien Sartika; Melina, Melina; Muhtar, Muhtar; Wahyuni, Resky Ayu; Sulastri, Elsa; Sulaeha, Sulaeha (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2025)
The cocoa pod borer (CPB), Conopomorpha cramerella Snellen, is one of the most significant pests of cocoa, capable of damaging pods and reducing production. Synthetic insecticides are predominantly used to control this pest; therefore, alternative methods that are environmentally friendly and do not harm non-target organisms are needed. This study aims to determine the role of beneficial insect occurrence, enhanced by insectary plants, in reducing the severity of pod damage and yield loss caused by CPB. The research was conducted by comparing two one-hectare farms, one with and one without insectary plants. The beneficial insects observed included pollinators, predators, parasitoids, decomposers, and herbivores. Their populations were higher on the farm with insectary plants than on the farm without, with pod damage severity of 16.8% and 32.8%, respectively. These data indicate that cultivating insectary plants on cocoa farms can aid in pest management, particularly for CPB, and has the potential to be implemented on a larger scale, as CPB attack intensity was lower on the farm with insectary plants.